SUFISM-BASED PHILOSOPHICAL CONSTRUCTION FOR THE APPLICATION OF MULTICULTURAL EDUCATION IN ISLAMIC EDUCATION - Hamka (An-Nahdlah: Journal of Islamic Studies, 2023)
Islamic Education in schools is facing new challenges with the development of technology and communication and also borderless civilization. Therefore, the need for an approach for these challenges is unavoidable. This study examines a education concept in order to answer the multiculturalism’s needs. Exploring the sufism concept and offer it as construction for Islamic Education. The research focus problem is to analyze sufism philosophy construct to be implemented in multiculturalism value in Islamic education. This qualitative research uses a library research design with a philosophical approach. The study indicates that multicultural education requires new philosophical constructs, especially in Islamic education. Therefore, the result of the study conclude that sufism offer concepts for multiculturalism in Islamic education as its able to bring three basic values: humanism, pluralism, and egalitarianism. This research also highlighted to be develop in more technical and practical form, including the complete construct of implementation in Islamic education in schools and university.